Agronomic Trait and Genetic Analysis of Latvian Flax Germplasm (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
There is a long history of flax cultivation in Latvia, and breeding programs were active until 1970’s, when flax breeding in Latvia was halted. Since 1992, the Agriculture Science Centre of Latgale (ASCL) has repatriated Latvian flax germplasm from various genebanks, as well as renewed limited breeding activities in flax. Currently, the ASCL holds a collection of 497 flax accessions, as well as 9865 accessions of various lines and hybrids developed at the LLZC since 1993. To assist in the characterization of this Latvian flax germplasm, we have utilised DNA markers to assess genetic diversity and relatedness, as well as surveying functional polymorphism. We have utilised Simple sequence repeat (SSR) markers developed from both genomic libraries as well as expressed sequences. The results of the DNA marker survey were utilised to determine the genetic polymorphism and relatedness within Latvian flax germplasm, and these results were compared with the analysis of agronomic traits carried out in field trials at the ASCL. The development of DNA markers linked to traits of agronomic importance will assist in the development of a Latvian flax breeding program. The use of DNA marker technology will allow more efficient assessment and rational utilization of Latvian flax germplasm.